Does the Chinese rule of law promote human rights?: the conception of human rights and legal reform in China - Lu, Yiwei (2016)
After more than three decades of legal reform under a promotion of the rule of law, it is opportune to assess and conceptualize the relationship between the legal reform and protection of human rights in China. The rule of law in China has been subjected to much controversy and debate. There are views that China at best desires and practices a rule by law under which the protection of human rights is a far-fetch goal. What further complicates the matter is that China’s legal reform is arriving at “crossroads” as it has exhausted most of the easy part of the reform. Legal reform today faces more difficulty in trying to accommodate and prioritize conflicting values and interests. This thesis aims to explore whether China’s legal reform towards the rule of law promote the protection of human rights. Using the distinction of thin and thick versions of rule of law, it is argued that the party-state aims to establish a Chinese rule of law integrating many basic standards of a thin rule of law. After decades of intensive reform many areas of law have incorporated certain principles of the thin rule of law. This process led to the advancement of human rights protection and rise of rights-consciousness. However, as the reform increasingly concerns more complicated issues that goes beyond “thin” solutions, the thesis argues that the conception of human rights come to play an important role in the decision-making.